Prevalence of the metabolic syndrome among children from six cities of China - Xu Haiquan; Li Yanping; Liu Ailing; Zhang Qian; Hu Xiaoqi; Fang Hongyun; Li Tingyu; Guo Hongwei; Li Ying; Xu Guifa; Ma Jun; Du Lin; et al. (BMC, 2012)
Abstract Background Metabolic syndrome (MetS) in childhood can increase the risk of cardiovascular disease, diabetes mellitus and dyslipidemia in adulthood, which is of increasing concern in transitional and advanced economies. The aim of the current study was to explore the prevalence of MetS among children from six cities of China. Methods A total of 8,764 children (4,495 boys, 4,269 girls) aged 7-11 years were randomly selected from 6 cities of China. MetS was mainly defined by the criteria proposed by International Diabetes Federation (IDF). Results The overall prevalence of MetS for children older than 10 years was 0.8% by IDF definition. Obese children had significantly higher MetS prevalence compared with their counterparts with overweight (6.6% vs. 0.9%, p < 0.01) and normal weight (6.6% vs. 0.05%, p < 0.01). The prevalence of abdominal obesity, high triglycerides, low high density lipoprotein cholesterol, hypertension and high glucose among obese children was 93.4%, 16.5%, 14.3%, 7.3% and 4.0%, respectively, which significantly higher than those among overweight children (37.0%, 6.1%, 10.0%, 4.2%, and 3.3%, respectively) and among normal weight children (1.2%, 3.3%, 4.0%, 1.7% and 2.5%, respectively). The proportion of children with at least one, two, and three items of the metabolic abnormalities were 25.0%, 5.4% and 0.9%, respectively. Metabolic abnormalities were also present in children under 10 years of age. Conclusions The early onset of MetS among children and relatively high proportions of children with at least one or two metabolic abnormalities in cities of China can increase the risk of developing MetS. It implies the necessity to take effective actions to control and prevent the rapid development of obesity among children in developing countries, especial those undergoing transition to a Western lifestyle.